VACCINATION REMINDER SYSTEM-SOLUTION FOR YOUNG MOTHERS - Apostolova Trpkovska, Marika; CHorbev, Ivan; Abazi Bexheti, Lejla; Jakovcevski, Bogoljub (My University, 2015)
Lately we are witnessing wonderful solutions that help ease the problems already exist. However, this emerging trend also means that experience in setting up viable environments is rare. Some see it as a challenge, but we think of it as a great opportunity. Web applications are the new swift in this decade and most of the developers are engaging their time to develop on web. This particular web application is made for immunization of the children in the dispersion of time from 0-18. The purpose of the application is to simplify and enhance the time scheduling of the immunization process where the families members such as parents will get the possibility to keep in touch with the schedule and be reminded of the immunization for their children.
Keywords: Vaccination; web application; young mothers; child vaccination; vaccine reminder; immunization